2000
DOI: 10.1007/s005860000166
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic vertical atlantoaxial instability: the risk associated with skull traction. Case report and literature review

Abstract: IntroductionThe stability of the atlantoaxial motion segment is unique. The lack of typical vertebral bodies and the arrangement of articular facets without protection against horizontal gliding make the articular system dependent mostly on the ligaments. Anterior C1-C2 dislocation is a rare and severe lesion in distraction caused by a predominantly ligamentous lesion, leading to displacement of the atlas on the axis [13].Vertebral displacements require reduction for neural decompression and stabilization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
0
27
0
4
Order By: Relevance
“…This seemingly simple procedure actually is very dangerous and highly technically demanding for several reasons. First, it is very difficult to determine how much force applied is appropriate and overdistraction of the C1-C2 complex can lead to immediate death of the patient [2,13]. For fear of this lethal complication of closed reduction, Yoon et al [19] adopted an operation-assisted reduction in their case to avoid overdistraction of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…This seemingly simple procedure actually is very dangerous and highly technically demanding for several reasons. First, it is very difficult to determine how much force applied is appropriate and overdistraction of the C1-C2 complex can lead to immediate death of the patient [2,13]. For fear of this lethal complication of closed reduction, Yoon et al [19] adopted an operation-assisted reduction in their case to avoid overdistraction of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…This suspicion of vertical AAD and our concern about the potential complications of traction together require that the initial care be especially attentive. Botelho et al [15] reported a case in 1997 of anterior AAD with a C1 anterior arch fracture. Skull traction with 4.02 lbs (1.5 kg) led to irreducible vertical AAD and patient death.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of three-dimensional imaging (CT scan and MRI reconstructions) and improvement in on-scene management, the incidence of vertical AAD might increase. Cervical traction is reported to lead to neurological deterioration and death, because it either reproduces the vertical distraction [15,18] or creates new injury by excessive stretching. Traction immobilization is usual in cases of cervical spine trauma, but must be avoided in cases of vertical AAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations